Cranial-thoracic trauma radiologic evaluation - G. N. Dorovskyh (Бюллетень сибирской медицины)
A total of 343 polytrauma patients (109 of them with cranio-thoracic trauma) of Omsk city emergency hospital № 1 during 2009—2011 were retrospectively analyzed with regard to supplementary and new findings obtained by digital X-ray and whole body multispiral computer tomographie. The optimum algorithm of diagnostics of patients with a cranio-thoracic trauma is developed.